Técnicas para mejoramiento de Lecto Escritura en los niños de cuarto año de Educación General Básica de la Unidad Educativa Fiscal Prócer José Cuero y Caicedo, de la parroquia San Isidro, cantón Morona provincia de Morona Santiago durante el año lectivo 2019 – 2020 - Suárez Barba, Janeliz Verónica (2020)
The Educational Intervention Project proposes to develop a portfolio of reading and writing to strengthen the teaching and learning of the boys and girls of Fourth Year of Basic General Education in order to respond to the existing need in the Prócer José Cuero y Caicedo school work that it will be done efficiently by implementing techniques that improve reading and writing. The Ministry of Education gave reading and writing texts to the different Educational Institutions of the community, material that is not enough to ensure that children read and write correctly, hence the desire to create techniques according to the age of the child. boy and girl because reading and writing are the basis of human education. The objective of this work is to determine if the use of techniques improves the reading and writing of boys and girls of the Fourth Year of Basic General of the Prócer José Cuero y Caicedo school. The Educational Intervention Project is vital in its execution and socialization since it tries to improve learning, being the beneficiaries the boys and girls of the San Isidro Parish of the Morona Canton with actions, immediate strategies carried out in the short term, promoting the area of Language and Literature the same that can be achieved with intensive campaigns in reading and writing and also the portfolio. The technique carried out on children in order to observe improvements after completing the work is the survey, in which we can observe positive results with regard to reading and writing, so we see a significant difference from when we started the work, the authorities, teachers, students, parents are satisfied with the work